The Roads to Congress 2024
XIX, 373 p. 15 illus., 10 illus. in color.
Keywords: This book assembles accomplished scholars and fresh new contributors to provide expert analysis on congressional campaigns and elections. Every election is pivotal, but few in American history have held the potential to upend the democratic norms and procedures undergirding our republican system of government. This book reveals the key campaign themes, candidates, issues, demographics, and strategies that determined control of the 119th Congress, and the future directions of politics in America. “A cogent analysis of the forces at work in congressional elections which make clear the evolution of politics in this century, and also durable evidence that the New Deal Coalition is gone, as are the assumptions about Congress and its politics which dominated the 20th century." -Keith Gåddie, Texas Christian University “Anyone looking to understand the electoral origins of the current sorry state of congressional affairs will learn much from these essays.” -Gary C. Jacobson, University of California at San Diego “The Roads to Congress 2024 points to the future of congressional elections and offers important perspectives on the state of American democracy.” -Lauren C. Bell, Randolph-Macon College Walter Wilson is Professor of Political Science at the University of Texas at San Antonio. He is the author of From Inclusion to Influence: Latino Representation in Congress and Latino Political Incorporation in America (2017) and co-editor of the Roads to Congress since 2018. Marcia L. Godwin is Associate Dean and Professor of Public Administration at the University of La Verne. She is co-editor and contributor, with Sean D. Foreman, of Local Government and Mayoral Elections in 21st Century America (2015). She is a long-time contributor to The Roads to Congress series and became a co-editor in 2016. Sean D. Foreman was Professor of Political Science at Barry University. He is co-editor of seven books, including The Roads to Congress series since 2016, with Palgrave Macmillan. Foreman was President of the Florida Political Science Association in 2012 and has served as Secretary of FPSA from 2015 to present.